The Role Of Parents In Preventing Choking In Children - Heru Suwardianto (Poltekkes Kemenkes Surakarta, 2021)
Background: Failure to feed babies is a choking-like problem often found in the community. Lactation management needs to be given to ensure successful implementation and provide better nutrition. The aim of this study is to analyzed the role of the family to preventing choking in children with supplementary feeding approach Methods: The research design is descriptive. The population was the familys with children with incidental sampling techniques. The research sample ware 44 respondents. Variables are the role of the family to preventing choking. Use Google Forms to survey data about mother-child cooperation with questions are Start Feeding as Early as Possible, Cooperation between mother and child, Role of family members, Feeding Schedule, and Eating Habits Result: The results of this study found that as far as the factors affecting eating are concerned, the index of starting eating as early as possible is 86.4%, and the index of mother-infant cooperation has an adequate impact on eating 50%. The index of the role of fathers and other family members shows that 84.1% of people are enough to influence eating. The indicators found no difficulty in determining the feeding schedule. It was found that the proportion that affected eating was 84.1%, while the eating habits indicators found that the proportion that affected eating was 84.1%. Conclusion: It is very important to provide anti-choking management when providing extra food, in the hope that there is no obstacle when providing extra food and satisfying children’s nutrition